Epidemiology of erectile dysfunction in men with diabetes mellitus: a study in a primary health care center in Indonesia (Medical Journal of Indonesia, 2020)
BACKGROUND Diabetes mellitus (DM) is one of the factors causing erectile dysfunction (ED) and may affect a person's quality of life. This study was aimed to describe the epidemiology of ED in men with DM in a primary health care. METHODS The study used a cross-sectional study design conducted from January to March 2017 at the Tlogosari Kulon Health Center, Semarang. There were 122 diabetic men who were all included in the study. The data were collected using interviewerassisted questionnaires. The status of ED was measured by the erectile dysfunction intensity scale adapted to the International Index of Erectile Function. RESULTS The results showed that the prevalence of diabetic men with ED was 84.4%. Most men with ED had age of ≥46 years (91.0%), experienced work stress (88.5%), had low physical activity (93.1%), had obesity (88.0%) of which 86.3% had central obesity, smoking (84.6%), had DM >5 years (91.2%), and took antihypertensive drugs (90.0%). The fasting blood glucose level of respondents ≥126 mg/dl was 86.0%, and 91.7% had sexual desire disorder. The duration of DM and aging are contributing factors of ED in males with DM, with a p-value of 0.016 and 0.013, respectively. CONCLUSIONS The prevalence of ED in primary health care is still high, and the determining factors were the duration of DM and aging. Public health centers are advised to undertake health promotion on the prevention of factors that can lead to sexual dysfunction in males with DM.